Effects of Epidermal Growth Factor and Myo-Inositol on Nuclear Configuration and Subsequent Embryonic Development of Sheep Oocytes - Omar Mardenli; Hadi Awad Hassooni; Mahdi Saleh Mohammad Alkerwi (Turkish Journal of Agriculture: Food Science and Technology)
Growth factors and vitamin-like substances have great positive importance in most biological interactions in the cellular level. The addition of these elements in the culture media will increase the yield of the resulting embryos and improve quality. We examined the effects of epidermal growth factor (EGF) and myo-inositol (MI) on meiotic maturation and yields of blastocyst of Awassi sheep oocyte across two experiments. The oocytes obtained were subjected into three treatments: A (without EGF nor MI), B (10 ng/ml EGF + 20 mmol/l MI) and C (50 ng/ml EGF +40 mmol/l MI). Oocytes were then cultured in Ham's F-10 medium supplemented with 5% (v: v) fetal calf serum and 40 ng/ml follicle - stimulating hormone. In the first experiment, during the 27-h culture period, the oocytes were assessed for germinal vesicle break down, metaphase-I and metaphase-II stages across three-time intervals (9, 21 and 27-h). Results of the experiment showed that EGF and MI enhanced the rates of germinal vesicle break down phase (1.53%; 27-h interval; lowest value), metaphase-I (33.87%; 21-h interval) and metaphase-II (89.23%; 27-h interval). In the second experiment, the oocytes incubated in treatment B achieved the highest rates of cleavage (81.96%), 2-8 cell (62.35%) and blastocyst (45.09%). It is concluded from the present study that incubating sheep oocytes in culture media containing a cocktail of EGF (10 ng/ml) and MI (20 mmol/l) significantly improves the rates of metaphase-II, fertilization and blastocyst rates.